2017
DOI: 10.3390/hydrology4040060
|View full text |Cite
|
Sign up to set email alerts
|

Regional Assessment of Groundwater Recharge in the Lower Mekong Basin

Abstract: Abstract:Groundwater recharge remains almost totally unknown across the Mekong River Basin, hindering the evaluation of groundwater potential for irrigation. A regional regression model was developed to map groundwater recharge across the Lower Mekong Basin where agricultural water demand is increasing, especially during the dry season. The model was calibrated with baseflow computed with the local-minimum flow separation method applied to streamflow recorded in 65 unregulated sub-catchments since 1951. Our re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 39 publications
(59 reference statements)
0
16
0
Order By: Relevance
“…Subsequently maps of the groundwater storage and the aquifer productivity were produced using assumptions of thickness, aquifer properties, and reported yields derived from the database, complemented by global published literature where local data was lacking. The renewability was then discussed using recently published groundwater recharge rates [33]. Each aquifers' groundwater development potential was then described based on these synthetized characteristics ( Figure 2).…”
Section: Groundwater Indicatorsmentioning
confidence: 99%
See 4 more Smart Citations
“…Subsequently maps of the groundwater storage and the aquifer productivity were produced using assumptions of thickness, aquifer properties, and reported yields derived from the database, complemented by global published literature where local data was lacking. The renewability was then discussed using recently published groundwater recharge rates [33]. Each aquifers' groundwater development potential was then described based on these synthetized characteristics ( Figure 2).…”
Section: Groundwater Indicatorsmentioning
confidence: 99%
“…Groundwater recharge is a crucial component to assess the potential of groundwater and its sustainability. Here, the recharge has been evaluated over the whole country using recently published data for Laos [33]. In this paper [33], the authors have identified 65 gauging stations across the LMRB, where daily streamflow data was available and not subject to dam regulations.…”
Section: Aquifer Rechargementioning
confidence: 99%
See 3 more Smart Citations